The Existence and Authority of the Regional Representative Council in Indonesia's Bicameral System - Dani Firlandani; Prastiwi, Dian Eka; Karhati, Tati (Sean Institute, 2025)
Indonesia's constitutional system adopts a bicameral system with the presence of the Regional Representative Council (DPD) as a representation of regional interests. However, the effectiveness of the DPD within the legislative system still faces various challenges, particularly due to its limited authority compared to the House of Representatives (DPR). The DPD only has the right to propose and provide considerations on certain draft laws but does not possess full legislative authority. This study aims to analyze the existence and authority of the DPD within Indonesia's bicameral system, identify the challenges it faces, and offer recommendations for strengthening its role. This study employs a normative method with a legislative and conceptual approach. The findings indicate that Indonesia's bicameral system is asymmetrical, where the authority of the DPD remains far below that of the DPR, differing from the bicameral systems in other countries such as the United States, where both legislative chambers hold full authority. This limitation creates a dilemma in representing regional interests in national policymaking. Therefore, reforming the authority of the DPD is necessary to achieve a more balanced legislative system that reflects the principles of inclusive democracy.